2017
DOI: 10.1136/vr.104386
|View full text |Cite
|
Sign up to set email alerts
|

Are serum amyloid A or D‐lactate useful to diagnose synovial contamination or sepsis in horses?

Abstract: Synovial sepsis in horses is life threatening and accurate diagnosis allowing prompt treatment is warranted. This study assessed the diagnostic value of serum amyloid A (SAA) and D-lactate in blood and synovial fluid (SF) as diagnostic markers of synovial sepsis in horses and correlated them with total nucleated cell count (TNCC), percentage of neutrophils (%N) and total protein (TP) in SF. Blood and SF SAA and D-lactate concentrations were determined in a case–control observational study including 112 horses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 29 publications
5
44
0
1
Order By: Relevance
“…Concentrations of SAA in plasma and synovial fluid are increased in horses with septic synovial disease (synovial fluid, mean of 39.2 mg/L and range of 0-368.9 mg/L; plasma, mean of 275.5 mg/L and range of 0-1421.8 mg/L) but not nonseptic (synovial fluid, mean of 0 mg/L and range of 0-29.7 mg/L; plasma, mean of 0.5 mg/L and range of 0-17 mg/L) or control groups. 73 A study examining SAA in experimentally induced inflammatory synovitis and septic arthritis found similar differences between groups in serum and synovial fluid SAA concentrations. 74 For the septic and aseptic groups, the mean peak synovial SAA concentrations were 135 mg/L (range, 60-555 mg/L) and 0 mg/L (range, 0-0), respectively, whereas the mean peak serum SAA concentrations were 663 mg/L (range, 217-1434 mg/L) and 0 mg/L (0-0), respectively.…”
Section: Serum Amyloid a And Diseases Of Equine Joints And Synovial Smentioning
confidence: 95%
“…Concentrations of SAA in plasma and synovial fluid are increased in horses with septic synovial disease (synovial fluid, mean of 39.2 mg/L and range of 0-368.9 mg/L; plasma, mean of 275.5 mg/L and range of 0-1421.8 mg/L) but not nonseptic (synovial fluid, mean of 0 mg/L and range of 0-29.7 mg/L; plasma, mean of 0.5 mg/L and range of 0-17 mg/L) or control groups. 73 A study examining SAA in experimentally induced inflammatory synovitis and septic arthritis found similar differences between groups in serum and synovial fluid SAA concentrations. 74 For the septic and aseptic groups, the mean peak synovial SAA concentrations were 135 mg/L (range, 60-555 mg/L) and 0 mg/L (range, 0-0), respectively, whereas the mean peak serum SAA concentrations were 663 mg/L (range, 217-1434 mg/L) and 0 mg/L (0-0), respectively.…”
Section: Serum Amyloid a And Diseases Of Equine Joints And Synovial Smentioning
confidence: 95%
“…The study by Robinson and others 2 also confirmed that one of the biggest advantages of SAA is that it also increases significantly in the blood of horses with septic arthritis. This is particularly interesting in cases in which synovial fluid withdrawal is not possible.…”
mentioning
confidence: 71%
“…SAA also has the potential to be used a monitoring and prognostic test, as hypothesised by Robinson and others 2017. 2 Despite the reported clinical advantages mentioned, SAA should still be considered as an adjunct diagnostic test.…”
mentioning
confidence: 99%
“…Monitoring response to treatment in horses with synovial sepsis has traditionally relied on white blood cell count and total protein determination in synovial fluid (SF) after repeated synoviocentesis 11. However, those SF parameters are affected by routine synoviocentesis, administration of intrasynovial medication and surgical synovial treatments, which makes their clinical interpretation difficult in some cases 2 7 12–16. The intrasynovial procedures listed seem to have a limited effect on blood SAA, which has been proposed as a potential parameter to monitor therapy and resolution of synovial sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…SAA can undergo a several thousand-fold increase from baseline values, followed by a rapid decrease in concentration once the infectious or inflammatory stimulus has been removed 2 3 8. A recent study compared SAA concentrations in blood and SF of horses with synovial sepsis to horses with non-septic synovial pathologies 12. Both blood and SF concentrations of SAA had diagnostic value in horses suffering from synovial sepsis 12.…”
Section: Introductionmentioning
confidence: 99%